Use of a Percutaneous Ventricular Assist Device for Treatment of Cardiogenic Shock due to Critical Aortic Stenosis - Frank, Christopher M. (2006)
We present the case of a 72-year-old woman who was transferred to our institution in cardiogenic shock and with multiple-organ failure, due to critical aortic stenosis. She was considered too high-risk to undergo aortic valve replacement. A TandemHeart® percutaneous ventricular assist device was used to stabilize the patient's condition before surgery, and she subsequently underwent successful aortic valve replacement. To our knowledge, this is the 1st report in the literature of this particular application of the TandemHeart device.